Huntingtin proteolysis releases non‐polyQ fragments that cause toxicity through dynamin 1 dysregulation. (14th July 2015) - El‐Daher, Marie‐Thérèse; Hangen, Emilie; Bruyère, Julie; Poizat, Ghislaine; Al‐Ramahi, Ismael; Pardo, Raul; Bourg, Nicolas; Souquere, Sylvie; Mayet, Céline; Pierron, Gérard; Lévêque‐Fort, Sandrine; Botas, Juan; et al.
Abstract Cleavage of mutant huntingtin (HTT) is an essential process in Huntington's disease (HD), an inherited neurodegenerative disorder. Cleavage generates N‐ter fragments that contain the polyQ stretch and whose nuclear toxicity is well established. However, the functional defects induced by cleavage of full‐length HTT remain elusive. Moreover, the contribution of non‐polyQ C‐terminal fragments is unknown. Using time‐ and site‐specific control of full‐length HTT proteolysis, we show that specific cleavages are required to disrupt intramolecular interactions within HTT and to cause toxicity in cells and flies. Surprisingly, in addition to the canonical pathogenic N‐ter fragments, the C‐ter fragments generated, that do not contain the polyQ stretch, induced toxicity via dilation of the endoplasmic reticulum (ER) and increased ER stress. C‐ter HTT bound to dynamin 1 and subsequently impaired its activity at ER membranes. Our findings support a role for HTT on dynamin 1 function and ER homoeostasis. Proteolysis‐induced alteration of this function may be relevant to disease.